Il Divo - Paolo Sorrentina (2008)
Winner of the Jury Award at the 2008 Cannes Film Festival, Il Divo is the controversial story of Guilio Andreotti (Toni Servillo). Calm, crafty, and inscrutable, Andreotti served seven terms as Italy s prime minister until the early 1990`s, when the world s most powerful Mafia declared war on him. Well-crafted and suspenseful, Il Divo is a story of politicking, corruption, scandal, and terrorism - and the man who sat through it all unscathed.
Keywords: Biography, Drama